Blueprint of 'fruit juice vending machine' /Nur Atikah Lokman...[et al.] - Lokman, Nur Atikah; Zamani, Nasirah; Mohd Zali, Siti Haimiera; Mohd Radzi, Nur Afiqah (2019)
"Fruit Juice Vending Machine" is one kind of vending machine that is processing the fruit into juice. It different with the juice vending machine are have in the market because in the market only provide one fruit. This vending machine have many features such as debit card payment system, detector and tracker system and touch screen LCD display. Our major target consumer for our fruit juice product university and college students and staffs. We focus our target market within Klang Valley, Malaysia because there are many local and private universities situated in this area. Our vending machine is the only vending machine that offers variety of fruit choices including orange, apple, banana and grapes in Malaysia. It is a great advantage to our company in producing the only vending machine with different choices of fruits and its special features. Although being the only fruit juice vending machine available in the market, there are few competitors in the marketplace such as conventional beverage vending machine, fruit juice bars and fresh orange vending machine. The price of our product which is the fruit juices is relatively cheaper compared to the indirect competitors. The channel of distribution for our product is sale directly to consumer model where the producer sells its product directly to the end consumer. A key feature of the vending machines is their location adaptability. The market communication tools used in introducing and promoting our fresh fruit juice product are public relation (publicity) and advertising. Our company will work together with the authority of university to make an announcement regarding our fresh juice product through university portal or websites. Type of advertising tool used in promoting our fresh fruit juice products are printed advertising such as posters and brochures.